Epicatechin and Catechin Modulate Endothelial Activation Induced by Platelets of Patients with Peripheral Artery Disease. (7th August 2014) - Carnevale, R.; Loffredo, L.; Nocella, C.; Bartimoccia, S.; Bucci, T.; De Falco, E.; Peruzzi, M.; Chimenti, I.; Biondi-Zoccai, G.; Pignatelli, P.; Violi, F.; Frati, G.
Abstract : Platelet activation contributes to the alteration of endothelial function, a critical initial step in atherogenesis through the production and release of prooxidant mediators. There is uncertainty about the precise role of polyphenols in interaction between platelets and endothelial cells (ECs). We aimed to investigate whether polyphenols are able to reduce endothelial activation induced by activated platelets. First, we compared platelet activation and flow-mediated dilation (FMD) in 10 healthy subjects (HS) and 10 patients with peripheral artery disease (PAD). Then, we evaluated the effect of epicatechin plus catechin on platelet-HUVEC interaction by measuring soluble cell adhesion molecules (CAMs), NOx production, and eNOS phosphorylation (p-eNOS) in HUVEC. Compared to HS, PAD patients had enhanced platelet activation. Conversely, PAD patients had lower FMD than HS. Supernatant of activated platelets from PAD patients induced an increase of sCAMs release and a decrease of p-eNOS and nitric oxide (NO) bioavailability compared to unstimulated HUVEC. Coincubation of HUVEC, with supernatant of PAD platelets patients, pretreated with a scalar dose of the polyphenols, resulted in a decrease of sCAMs release and in an increase of p-eNOS and NO bioavailability. This study demonstrates that epicatechin plus catechin reduces endothelial activation induced by activated platelets.